(untitled) (Malaysian Journal of Civil Engineering, 2017)
Serious scaling effect has been overlooked since the concept of modelling technique was introduced. Even though dimensional analysis is the best tool when relating the model-prototype however, the scaling of stresses needs yet to be justified. This paper demonstrates the presence of scaling effect by comparing 3 model studies based on a centrifugal and conventional small model test using sand as an embedment media. This enables potential errors in direct extrapolation of the latter to field scale to be evaluated.